Depressive symptomatology, weight status and obesogenic risk among Australian adolescents: a prospective cohort study. Issue 3 (14th March 2016) - Hoare, Erin; Millar, Lynne; Fuller-Tyszkiewicz, Matthew; Skouteris, Helen; Nichols, Melanie; Malakellis, Mary; Swinburn, Boyd; Allender, Steven
Abstract : Objectives: Adolescence is a period of increased risk for mental health problems and development of associated lifestyle risk behaviours. This study examined cross-sectional and longitudinal associations between obesogenic risk factors, weight status, and depressive symptomatology in a cohort of Australian adolescents. Design: Prospective cohort study. Setting: The study used repeated measures data from the Australian Capital Territory (ACT) It's Your Move project, an Australian community-based obesity prevention intervention. Intervention effect was non-significant therefore intervention and comparison groups were combined in this study. Participants: Total sample was 634 secondary school students (female n=338, male n=296) with mean age 13 years (SD=0.6) at baseline (2012) and 15 years (SD=0.6) at follow-up (2014) recruited from 6 government secondary schools in the ACT. Primary and secondary outcomes measures: Primary outcome was depressive symptomatology measured by Short Mood and Feelings Questionnaire. Secondary outcomes were weight status, physical activity, screen time and diet related measures. Results: Increased physical activity was associated to lower depressive symptomatology among males (OR=0.35, p<0.05). Sweet drink (OR=1.15, p<0.05) and takeaway consumption (OR=1.84, p<0.05) were associated with higher levels of depressive symptomatology among females at follow-up. Males who were classified as overweight or obese at baseline, and remained so over the study period, were at increased risk of depressive symptomatology at follow-up (b=1.63, 95% CI 0.33 to 2.92). Inactivity among males over the 2-year study period was predictive of higher depressive symptomatology scores at follow-up (b=2.55, 95% CI 0.78 to 4.32). For females, those who increased their consumption of takeaway foods during the study period were at increased risk for developing depressive symptomatology (b=1.82, 95% CI −0.05 to 3.71). Conclusions: There are multiple, probably complex, relationships between diet, physical activity and outcomes of obesity and mental health as well as between the outcomes themselves. Healthier diets and increased physical activity should be foundations for healthier body weight and mental health. Trial registration number: ACTRN12615000842561; Results.